Solvent-Free Synthesis of Functionalized Pyridine Derivatives Using Wells— -Dawson Heteropolyacid as Catalyst - Sanchez, Laura Mabel (2011)
Wells-Dawson heteropolyacids (H6P2W18O62·24H2O) were used as catalysts in the Hantzsch-like multicomponent condensation reaction with 3-formylchromones as aldehyde component, a β-ketoester and ammonium acetate, under solvent-free conditions at 80 °C. Although the desired products were obtained, functionalized pyridines were the main reaction product and became the alternative route to dihydropyridine ring formation. Based on the proposed mechanisms for the formation of each of the obtained products, the multicomponent reaction was modified to afford only the functionalized pyridines (60–99%). Our procedure represents a clean alternative for the synthesis of several highly functionalized pyridines.